2023
DOI: 10.1111/nmo.14573
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome in adolescents with irritable bowel syndrome and changes with percutaneous electrical nerve field stimulation

Abstract: Background Irritable bowel syndrome (IBS), a disorder of the gut–brain axis, is affected by the microbiome. Microbial studies in pediatric IBS, especially for centrally mediated treatments, are lacking. We compared the microbiome between pediatric IBS patients and healthy controls (HC), in relation to symptom severity, and with percutaneous electrical nerve field stimulation (PENFS), a non‐invasive treatment targeting central pain pathways. Methods We collected a stool sample, questionnaires and a 1–2 week sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although speculative, it is conceivable that altered brain connectivity may be responsible for the long‐term improvements. Other proposed PENFS mechanisms to some degree supported by data include: (1) restoration of inefficient cardiac vagal regulation or autonomic control, (2) alterations in intestinal microbial pathways, and (3) neuromodulation of the limbic system, previously demonstrated in a preclinical study 16,17,39,40 . Multiple, conjoined mechanisms may also be at play and more studies of pathophysiology and long‐term effects of PENFS are needed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although speculative, it is conceivable that altered brain connectivity may be responsible for the long‐term improvements. Other proposed PENFS mechanisms to some degree supported by data include: (1) restoration of inefficient cardiac vagal regulation or autonomic control, (2) alterations in intestinal microbial pathways, and (3) neuromodulation of the limbic system, previously demonstrated in a preclinical study 16,17,39,40 . Multiple, conjoined mechanisms may also be at play and more studies of pathophysiology and long‐term effects of PENFS are needed.…”
Section: Discussionmentioning
confidence: 94%
“…Other proposed PENFS mechanisms to some degree supported by data include: (1) restoration of inefficient cardiac vagal regulation or autonomic control, (2) alterations in intestinal microbial pathways, and (3) neuromodulation of the limbic system, previously demonstrated in a preclinical study. 16,17,39,40 Multiple, conjoined mechanisms may also be at play and more studies of pathophysiology and long-term effects of PENFS are needed. These data are suggestive that PENFS at least in part targets the gut-brain axis dysregulation of DGBI.…”
Section: Discussionmentioning
confidence: 99%
“…PENFS also improved these outcomes at 3 weeks and 3 months in children with functional dyspepsia ( 9 ). Another proposed mechanism for PENFS includes microbiome changes after treatment, which may also reflect changes in vagal anti-inflammatory pathways ( 39 ). In a recent study, patients with IBS, post-PENFS treatment, were found to have decreased Clostridial species and long chain fatty acid microbial pathways that have been implicated in the pathophysiology of IBS ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechanism for PENFS includes microbiome changes after treatment, which may also reflect changes in vagal anti-inflammatory pathways ( 39 ). In a recent study, patients with IBS, post-PENFS treatment, were found to have decreased Clostridial species and long chain fatty acid microbial pathways that have been implicated in the pathophysiology of IBS ( 39 ). In that study, improvements in abdominal pain, functioning, and catastrophizing were noted as well.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there has been increasing interest in examining the microbiome of patients with various pain disorders, However, there is a lack of studies in the pediatric population. A recent study evaluated changes in the microbiome of adolescents with IBS after PENFS treatment, The microbiome showed decreased Clostridial species and long chain fatty acid (LCFA) microbial pathways post treatment (25). A future goal could be to examine the microbiome of children with other DBGIs besides IBS and changes in the microbiota secondary to PENFS.…”
Section: Future Directions and Clinical Implicationsmentioning
confidence: 99%